A simple and universal measurement method for the pulsed IV characteristics of high‐power amplifiers. Issue 17 (13th June 2022) - Fu, Chao; He, Tian‐Wei; Fang, Wen‐Rao; Huang, Wen‐Hua; Guo, Le‐Tian; Wang, Lu‐Lu; Li, Jia‐Wei; Zhong, Sheng
Abstract: This letter proposes a simple and universal method to measure the current within the pulse of pulsed power amplifiers. Pulsed high‐power amplifiers have large current within the pulse and the current changes very quickly when the pulse turns on or turns off. The conventional method of using a current clamp to measure the current within the pulse needs a large current clamp, which will increase the parasitic inductance of power path and result in a large voltage overshoot that can damage the amplifier. The proposed method measures the average current under several different pulse widths; thus, the current can be concluded with these average currents. Since current clamp is avoided, the proposed method can significantly reduce the parasitic inductance and voltage overshoot. Experiment shows that the voltage overshoot is significantly reduced by the proposed method. The result of the current value calculated by the proposed method is consistent with that measured by the conventional method, and the difference is within 2%.